Studi Komparasi Booklet Konvensional dan Digital dalam Peningkatan Pemahaman dan Perubahan Sikap Ibu terhadap ASI Eksklusif di Kota Mataram: Comparative Study of the Effectiveness of Convensional and Booklet Digitals in Increasing Understanding and Changing Maternal Attitudes towards Exclusive Breastfeeding in Mataram City - Paramita, Farah; Al-Irsyad, Muhammad; Laksana, Dian Puspitaningtyas; Katmawanti, Septa; Sharoni, Siti Khuzaimah Ahmad; Samah, Dea Aflah; Wahyuni, Oktavia Sri; Putri, Fatiya Rizka; Rabbani, Muhammad Fahmi; An-Khofiyya, Nida; Pahlevi, Reza (Universitas Airlangga, 2026)
Background: Child malnutrition is a global challenge in Indonesia, specifically in Mataram City, primarily attributed to the low coverage of exclusive breastfeeding. One potential strategy to address this challenge is increasing health knowledge through health promotion media, such as conventional and digital booklet. Objectives: This study aims to implement interventions using both conventional and digital booklet media, compare the two types of booklet, and determine which type is more accepted by the community. Methods: A pre-experimental method with a cross-sectional design was conducted using a one-group pretest-posttest approach comprising 96 mothers with infants aged 6 to 24 months in the Cakranegara and Ampenan Puskesmas areas. Data were collected using questionnaires to assess maternal knowledge and attitude both before and after the intervention. The differences in knowledge and attitude were analyzed using the Wilcoxon Test. Results: The results showed that the intervention of digital booklet did not produce a statistically significant difference in the enhancement of knowledge or attitude among the respondents (p-value>0.05). Conversely, the intervention of conventional booklet showed a statistically significant difference in attitude (p-value<0.05), and no significant difference was observed in knowledge (p-value>0.05). Conclusions: The intervention of conventional booklet produced a greater increase in knowledge and attitude compared to digital booklet. Therefore, it can be concluded that conventional booklet is more accepted by the community than digital.